A Ventral Hernia-repair–related Mycobacterium mageritense Mesh Infection Treated with NPWT without Mesh Removal. Issue 9 (7th September 2021) - Ando, Junji; Miyata, Riyo; Harada, Masayuki; Takeuchi, Mika; Kasahara, Kei; Yoshimoto, Yuji; Koyama, Fumikazu; Kuwahara, Masamitsu
Abstract : Summary: Abdominal hernias are often repaired using prosthetic mesh, which is susceptible to infections. Normally, it is necessary to remove the mesh. However, successful mesh salvation with negative-pressure wound therapy (NPWT) has recently been reported. We encountered Mycobacterium(M) mageritense infection after hernia repair using the mesh. M. mageritense is classified as a fast-growing nontuberculous mycobacterium, but few cases have been reported. Nontuberculous mycobacterium can cause rare chronic infections. Skin and soft-tissue infections by nontuberculous mycobacterium involving localized abscess formation and chronic abscesses under various situations have been reported. We report an 85-year-old woman in whom a ventral hernia repair-related M. mageritense mesh infection was treated with NPWT without mesh removal. The hernia was repaired using Bard Ventralex mesh. Pus discharge was seen on the seventh postoperative day, and there was a small area of necrosis under the mesh. From the 13th postoperative day, NPWT was performed for 4 weeks. On the 29th postoperative day, a M. mageritense infection was diagnosed, which was resistant to multiple drugs. After the NPWT, most of the wound showed good granulation tissue formation. In conclusion, the mesh used to repair a hernia became infected with M. mageritense, but NPWT was able to salvage it. In cases of mesh infection involving small necrotic areas, performing NPWT under the guidance of an infectious disease expert may make it possible to preserve the mesh.